Parametric Optimization of Electrical Discharge Machining (EDM) Process on Din 1.2714 Steel - Ripendeep Singh Sidhu, Kiranpreet Singh Kang (International Journal of Advanced Science and Technology, 2020)
Electrical discharge machining is process in which desired shape is obtained by using electrical discharges. EDM is also known as spark machining, die sinking; wire burning.DIN 1.2714(steel) is mostly used in the industries. Many applications of DIN1.2714 (steel) are forging tools, dies of all sorts, hot forging, pressing tools, moulds, bushings and piercers etc. This steel is extensively used in forging dies and there is great need on carrying research on this material so that EDM parameters are to be optimized to get higher MRR and lower TWR. Experiment was performed by using An L27 orthogonal array at three different levels for five machining parameters. These experiments were performed with two successive trials in a random order. Influence of each variable obtained through ANOVA analysis.